Rapid test to detect insecticide resistance in field populations of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Mao, Kai-Kai; Li, Hong-Ran; Zhu, Jing-Yun; Jin, Ming-Hui; Wang, Peng; Peng, Yan; Xiao, Yu-Tao (Frontiers in Physiology, 2023)
The development of insecticide resistance in Spodoptera frugiperda populations is a serious threat to the crop industry. Given the spread of invasive resistant populations, prospective monitoring should be accelerated, and the development of diagnostic tools for rapid and accurate assessments of insecticide resistance is essential. Here, we describe a diagnostic kit that enables the rapid detection of resistance to chlorpyrifos, bifenthrin, deltamethrin, lambda-cyhalothrin, phoxim, chlorantraniliprole and chlorfenapyr within 1-2 h in S. frugiperda at diagnostic doses of 0.98, 0.84, 0.38, 1.64, 0.0082, 1.75 and 0.65 μg/cm 2 , respectively. The linear equation between mortalities under diagnostic doses and actual resistance ratios measured by the diet-overlay bioassay was determined. The high correlation indicates that the insecticide resistance levels diagnosed by the kit were consistent with the results of the diet-overlay bioassay.Moreover, we found a significant negative correlation between diagnostic mortality and the likelihood of control failure for bifenthrin (r = −0.899, P = 0.001), deltamethrin (r = −0.737, P = 0.024) and lambda-cyhalothrin (r = −0.871, P = 0.002). The insecticide resistance diagnostic kit for S. frugiperda is a user-friendly tool (portable, short detection time). Its excellent performance qualifies the kit as a reliable screening tool for identifying effective insecticides in sustainable resistance management.